2023
DOI: 10.3390/foods12061277
|View full text |Cite
|
Sign up to set email alerts
|

“Got Milk Alternatives?” Understanding Key Factors Determining U.S. Consumers’ Willingness to Pay for Plant-Based Milk Alternatives

Abstract: Milk is an important dairy product in U.S. food retail. Lifestyle changes toward climate-conscious consumption, animal welfare, and food safety concerns have increased the popularity of plant-based milk alternatives. This study is focused on such beverages and provides insights and best practice recommendations for marketing managers in the U.S. food retail sector. An online survey was distributed to explore factors explaining the intentions of U.S. consumers to purchase and pay a premium for plant-based milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 75 publications
1
12
0
Order By: Relevance
“…Preferences for product attributes—appearance, sensory aspects, nutritional value, and environmental benefits—positively correlated with WTP, mirroring the findings of Rombach et al [ 55 ], who identified environmental, food safety, health, and sustainability concerns as influential predictors of consumer behaviors. Among the attributes, environmental benefits exerted the most substantial positive impact on WTP, a finding that is consistent with Rombach et al’s study [ 13 ]. Their research emphasized the significant effect of animal welfare considerations, a component of environmental consciousness, on the WTP premium for PBM.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Preferences for product attributes—appearance, sensory aspects, nutritional value, and environmental benefits—positively correlated with WTP, mirroring the findings of Rombach et al [ 55 ], who identified environmental, food safety, health, and sustainability concerns as influential predictors of consumer behaviors. Among the attributes, environmental benefits exerted the most substantial positive impact on WTP, a finding that is consistent with Rombach et al’s study [ 13 ]. Their research emphasized the significant effect of animal welfare considerations, a component of environmental consciousness, on the WTP premium for PBM.…”
Section: Discussionsupporting
confidence: 90%
“…The consumption of PBM has seen a significant increase in the global food industry in recent years due to heightened awareness among consumers about health and environmental issues [ 13 ]. The global market share of PBM has risen from below 10% in 2015 to over 13% by 2018 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, price, brand, and whether there was a promotion or not affected the decision to purchase plant-based beverages ( Table 2 ). Studies in the literature have also shown that several factors including nutrient content, diet, socioeconomic status, health effects, environmental protection, and sustainability influenced the preference and purchasing behavior for plant-based beverages [ 10 , 17 , 57 , 58 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…First, the mean value of the price elasticity of demand is calculated based on the collected annual data of raw milk prices from 2016 to 2022. Then, the predicted price and demand elasticity coefficient are applied to predict the dairy consumption in the future by Formula (11). We predicted the raw milk price in the next year based on RMP-CPR.…”
Section: Consumer Purchasing Behavior Analysis Based On Raw Milk Pric...mentioning
confidence: 99%
“…Demographic and socioeconomic factors, such as price, availability, awareness, and convenience, could affect dietary behavior [10]. Food curiosity and food price inflation were identified as relevant for both willingness to buy and willingness to pay a price premium [11]. By virtue of low price elasticity, increased prices may negatively affect the household resources available to purchase other key sources of nutrients [12].…”
Section: Introductionmentioning
confidence: 99%